Penerapan Statistical Process Control (SPC) dan Failure Mode Effect Analysis (FMEA) pada Proses Produksi Tisu Wajah - Erni Krisnaningsih; Sri Mukti Wirawati; Yan Febriansyah (Jurnal PASTI (Penelitian dan Aplikasi Sistem dan Teknik Industri), 2020)
The purpose of this study is to identify the type of defects that occur, identify the causative factors of disability using SPC and FMEA methods to improve the competitiveness of network companies in PT. Xyz. From the results of the control map there is 1 point above the UCL limit that occurred in the 6th month. Furthermore, analysis with pareto diagram, which is known to be the most dominant defect there are 3 or 30% piece is not up to standard, 27% folds are not aligned, 23% sealing results are not perfect. From the highest percentage of analysis with fish bone diagrams, there are several factors that cause differences, namely human factors are less thorough, machines lack maintenance, methods are not up to standard, hygiene environment is poorly maintained and raw materials are not good. Furthermore, the analysis using FMEA to determine the priority scale obtained that the priority scale based on the RPN table including the sealing result was difficult to open with a total of RPN 338.8, the folds were not aligned with the total RPN of 212 and the pieces were not symmetrical with a total of RPN 106.5. Based on rpn table, proposed repair using 5W+1H obtained by proposed daily briefaing, scheduled machine checking, checking before materials are used, ensuring the settings on the machine according to standards.